Fractional cointegration in US term spreads - Guglielmo Maria Caporale; Luis A. Gil-Alana (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
This note examines the stochastic properties of US term spreads with parametric and semi-parametric fractional integration techniques. Since the observed data (rather than the estimated residuals from a cointegrating regression) are used for the analysis, standard methods can be applied. The results indicate that US Treasury maturity rates are I(1) in most cases, although the order of integration decreases with maturity. Further, mean reversion occurs for the 5, 7 and 10 year rates as well as for several term spreads, suggesting that the expectation hypothesis of the term structure is satisfied empirically.
Keywords: C22; E43; 330; Term structure; long memory; fractional integration; fractional cointegration; Zinsstruktur; Öffentliche Anleihe; Kointegration; Schätzung; USA